168k views
5 votes
12 = 5x - 13x - 44

Please help me

User Jortega
by
5.6k points

1 Answer

5 votes

eorder the terms:

12 = -44 + 5x + -13x

Combine like terms: 5x + -13x = -8x

12 = -44 + -8x

Solving

12 = -44 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.

12 + 8x = -44 + -8x + 8x

Combine like terms: -8x + 8x = 0

12 + 8x = -44 + 0

12 + 8x = -44

Add '-12' to each side of the equation.

12 + -12 + 8x = -44 + -12

Combine like terms: 12 + -12 = 0

0 + 8x = -44 + -12

8x = -44 + -12

Combine like terms: -44 + -12 = -56

8x = -56

Divide each side by '8'.

x = -7

Simplifying

x = -7

User Girish Hosamani
by
5.2k points